A candidate multi‐epitope vaccine against Lumpy skin disease. Issue 6 (7th November 2022) - Uddin, Md Bashir; Tanni, Fatema Yeasmin; Hoque, Syeda Farjana; Sajib, Emran Hossain; Faysal, Md Atik; Rahman, Md Anisur; Galib, Asaduzzaman; Emon, Ahsan Al; Hossain, Md Mukter; Hasan, Mahmudul; Ahmed, Syed Sayeem Uddin
Abstract: Lumpy skin disease (LSD) is a fulminant infectious disease that mostly affects cattle and causes considerable economic loss throughout the globe. This study was conducted to develop a new multi‐epitope‐based vaccine against LSD that can elicit immunological responses using an in silico reverse vaccinology approach. Initially, three antigenic proteins, protein E5, E3 ubiquitin‐protein ligase LAP and 62 kDa protein, were manipulated to recognize potential T‐cell and B‐cell epitopes. To identify superior epitopes, a variety of bioinformatic techniques including antigenicity testing, transmembrane topology screening, allergenicity assessment, conservancy analysis, and toxicity evaluation were used. Finally, three new subunit vaccines (construct V1, V2 and V3) were developed employing the most effective epitopes, suitable adjuvants, pan HLA DR‐binding epitope (PADRE) and linkers. Then, based on the antigenicity, solubility, and validation score of the 3D structures, construct V2 was chosen as one of the best candidate vaccines. The results of the molecular dynamic simulation and disulphide engineering indicated that the vaccine (construct V2) was stable. Additionally, the immunological simulation findings supported the vaccine candidate's ability to trigger humoral and cellular immune responses. Further validation of the proposed vaccine candidate may necessitate additional in vitro and in vivo investigations.